A Path to Greater Credibility: Large-Scale Collaborative Education Research. (December 2019) - Makel, Matthew C.; Smith, Kendal N.; McBee, Matthew T.; Peters, Scott J.; Miller, Erin M.
Concerns about the replication crisis and unreliable findings have spread through several fields, including education and psychological research. In some areas of education, researchers have begun to adopt reforms that have proven useful in other fields. These include preregistration, open materials and data, and registered reports. These reforms offer education research a path toward increased credibility and social impact. In this article, we discuss models of large-scale collaborative research practices and how they can be applied to education research. We discuss five types of large-scale collaboration: participating teams run different studies, multiteam collaboration projects, collaborative analysis, preregistered adversarial collaboration, and persistent collaboration. The combination of large-scale collaboration with open and transparent research practices offers education researchers opportunity to test theories, verify what is known about a topic, resolve disagreements, and explore new questions.